Optimal location of multi-type FACTS devices in a power system by means of genetic algorithms. - Gerbex, S. (IEEE Transactions on power systems)
This paper presents a genetic algorithm to seek the optimal location of multi-type FACTS devices in a power system. The optimizations are performed on three parameters: the location of the devices, their types and their values. The system loadability is applied as a measure of power system performance. Four different kinds of FACTS controllers are used and modeled for steady-state studies: TCSC, TCPST, TCVR and SVC. Simulations are done on a 118-bus power system for several numbers of devices. Results show the difference of efficiency of the devices used in this context. They also show that the simultaneous use of several kinds of controllers is the most efficient solution to increase the loadability of the system. In all the cases (single- and multi-type FACTS devices), we observe a maximum number of devices beyond which this loadability cannot be improved